Діагностика туристичної активності регіону на засадах економічної компаравістики - Почерніна, Наталя Вікторівна; Васильченко, Олена Олегівна; Pochernina, Natalia; Vasylchenko, Olena (Запоріжжя : 2023, 2023)
UA: Обґрунтовано застосування теорії комправістики до аналізу сфери туризму на регіональному рівні. Проаналізовано індикатори туристичної активності регіонів та запропонована класифікація її напрямів. Виявлено регіональні відмінності в розвитку туристичної активності на основі обчислення інтегрального індексу. Доведено, що рейтингова оцінка туристичної активності регіонів дозволяє діагностувати наявний диспаритет як в межах галузі, так і в межах країни. EN: The purpose of this study is to diagnose the tourist activity of the regions of Ukraine in the pre-war period in order to identify common and special features. The authors set the following tasks: 1) justify the use of the theoretical foundations of comparative studies for the analysis of the tourism sphere; 2) to improve the analysis of tourist activity in the region by classifying its directions and selecting their corresponding indicators; 3) to diagnose disparities in the tourism activity of the regions and propose ways to reduce of them. Research results. It has been proven that tourism is a complex system that produces economic, social, environmental and other effects at the micro, metho and macro levels and combines many institutions whose behavior affects the configuration of "disorder - order". In this regard, the conceptual foundations of the theory of comparative studies were used to identify specific features of regions in tourism activity. The classification of the directions of tourist activity was proposed for this purpose. The integral index was calculated based on a set of indicators of tourist activity. The regions of Ukraine were divided according to the level of tourist activity. Conclusion. It was found that regions with more developed tourism infrastructure showed a higher integral index. The disparity "resources - return" was revealed as a result of ineffective tourism policy of individual regions. Certain measures to overcome this disparity have been proposed. They are aimed at consolidating the efforts of private business, the population, local and central authorities for the development of tourism in the regions.
Diagnostics of region´s tourist activity on the bases of comparative economics
Keywords: туризм; туристична активність; регіональні відмінності; економічна компаравістика; діагностика; рейтингова оцінка; tourism; tourist activity; regional differences; comparative economics; diagnostics; rating assessment